Effects of essential oil extracted from Artemisia argyi leaf on lipid metabolism and gut microbiota in high-fat diet-fed mice - Wang, Kaijun; Ma, Jie; Li, Yunxia; Han, Qi; Yin, Zhangzheng; Zhou, Miao; Luo, Minyi; Chen, Jiayi; Xia, Siting (Frontiers in Nutrition, 2022)
Artemisia argyi leaf is a well-known species in traditional Chinese medicine and its essential oil (AAEO) has been identified to exert very physiological activities. The aim of present study was conducted to investigate the effects of AAEO on lipid metabolism and the potential microbial role in high-fat diet (HFD)-fed mice. A total of 50 male mice were assigned to five groups feeding with a control diet (Con), a high-fat diet (HFD), and the HFD plus with the low (LEO), medium (MEO) and high (HEO) doses of AAEO. The results demonstrated that dietary HFD markedly increased the body weight gain compared with the control mice (p < 0.05), while mice in the HEO group showed a lower body weight compared to the HFD group (p < 0.05). The weight of fatty tissues and serum lipid indexes (TBA, HDL and LDL level) were increased in response to dietary HFD, while there was no significant difference in AAEO treated mice (p < 0.05). The jejunal villus height was dramatically declined in HFD fed mice compared with the control mice, while HEO resulted in a dramatically higher villus height than that in HFD group (p < 0.05). At the genus level, the relative abundance of Bacteroides was greater (p < 0.05) in the feces of Con group when compared to the HFD and EO group. By contrary, the abundance of Muribaculum was less in the Con group than in the HFD and EO group (p < 0.05). Although the Muribaculum in the EO group was lower than that in the HFD group, it was no statistically notable difference in HFD and EO group (p > 0.05). Simultaneously, the relative abundance of Alistipes (p < 0.05) and Rikenella (p < 0.05) was also dramatically higher in Con group than HFD and EO group. The abundance of norank_f__norank_o__Clostridia_UCG-014 was lower in the HFD or EO group than in the Con group (p < 0.05). In conclusion, the results suggested that HEO could affect body weight and lipid metabolism without gut microbes in ICR mice, and it was beneficial for the structure of the jejunum epithelial tissue